The Effect of Working Capital on Profitability in Pulp and Paper Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2015 – 2020 - Akhmad Agung Cahyono; Purnamawati Purnamawati (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The purpose of this study was to determine the effect of working capital elements consisting of cash turnover, receivables turnover, and inventory turnover on profitability (ROA) in pulp and paper sub-sector companies listed on the Indonesia Stock Exchange in 2015-2020. This study uses quantitative methods with sampling technique using purposive sampling. This study uses secondary data with multiple regression analysis. The hypothesis of this research is the effect of cash turnover, receivables turnover, and inventory turnover has a positive and significant effect on profitability partially and simultaneously. The conclusions of this study are (1) the cash turnover variable (X1) has a negative and insignificant effect on profitability (2) The receivables turnover variable (X2) has a negative and insignificant effect on profitability (3) The inventory turnover variable (X3) has a positive and no positive effect. significant on profitability (4) Variables cash turnover, accounts receivable turnover, and inventory turnover does not simultaneously affect profitability.